Black bear density and habitat use variation at the Sierra Nevada‐Great Basin Desert transition. Issue 3 (3rd January 2023) - Sultaire, Sean M.; Kawai‐Harada, Yuki; Kimmel, Ashley; Greeson, Emily M.; Jackson, Patrick J.; Contag, Christopher H.; Lackey, Carl W.; Beckmann, Jon P.; Millspaugh, Joshua J.; Montgomery, Robert A.
Abstract: In the first 2 decades of the twenty‐first century, American black bear ( Ursus americanus ) populations rebounded with range expansions into areas where the species was previously extirpated. While there are a number of factors that limit range expansion, habitat quality and availability are among the most important. Such factors may be particularly important in western Nevada, USA, at the transition zone of the Sierra Nevada and the Great Basin Desert. We deployed a multi‐faceted data collection system including motion‐sensitive cameras, noninvasive hair sampling and genotyping, and global positioning system (GPS) tracking. We analyzed data using spatial capture‐recapture to estimate population density and dynamic occupancy models to estimate habitat use. Black bear habitat use and density were substantially higher in the Sierra Nevada than the Great Basin Desert and had strong positive relationships with the presence of conifer land cover in the transition zone. The average black bear density was >4 times higher in the mixed‐conifer forests of the Sierra Nevada (12.4 bears/100 km 2 ) than in desert mountain ranges with piñon ( Pinus monophylla )‐juniper ( Juniperus spp.) woodland (2.7 bears/100 km 2 ). The low‐elevation shrub and grassland portions of the study area had even lower estimated black bear density (0.6 bears/100 km 2 ) and probability of use (0.03, 95% CI = 0.00–0.09). Across these spatially variable configurations in black bear density, we estimated the population size to be 418 individuals (95% CI = 239–740). Declining density towards the range edge, coupled with a relatively stable range of black bears in Nevada observed since 2000, suggests that further species range expansion into the western Great Basin may be limited by habitat quality and availability. Abstract : Black bears are at the edge of their range in the western Great Basin in Nevada. We estimated that black bear density was 4 times lower in piñon‐juniper woodland in the Great Basin compared to mixed conifer in the nearby Sierra Nevada. Low densities in piñon‐juniper woodland may limit black bear range in the Great Basin.